Immunomodulatory potential of ethanolic extract from Momordica charantia L. in mastic cow's milk (Research, Society and Development, 2021)
Milk cattle farming is one of the main pillars of the Brazilian economy. Unfortunately, several factors affect the quality and quantity of milk produced in a milk units, among them a mastitis. Mastitis is a disease characterized by inflammation in the mammary glands, having several causes. The control of mastitis is done from preventive handling and with the use of intramammary antibiotic. Frequent use of antibiotics can cause resistance, making subsequent treatments difficult. Therefore, the study of phytotherapics in the control of mastitis has become more frequent and with promising results. Several plants and natural extracts have already been tested in mastitis control. The studied plant in question is called Momordica charantia, popularly known as Melão de São Caetano. This plant has demonstrated numerous medicinal effects for different purposes. This work aims to analyze the immunomodulatory potential of Momordica charantia on milk cells of mastitic cows. Twenty samples of cow's milk were collected, ten of which were healthy cows and ten cows with clinical mastitis. Subsequently, cell viability analysis, superoxide anion release, superoxide dismutase enzyme dosage, phagocytosis and microbicidal activity were performed. In samples containing extract a decrease in superoxide anion and superoxide dismutase enzyme was probably due to the escape mechanism of bacteria, and an increase in microbicidal activity and phagocytosis suggesting that the extract of Momordica charantia is an immunomodulatory potential against mastitis bovine.